2022
DOI: 10.1002/advs.202103628
|View full text |Cite
|
Sign up to set email alerts
|

FIONA1‐Mediated m6A Modification Regulates the Floral Transition in Arabidopsis

Abstract: N6‐methyladenosine (m6A) mRNA modification represents the most widespread form of internal modifications in eukaryotic mRNAs. In the model plant Arabidopsis thaliana, those known methyltransferases mainly deposit m6A at their target transcripts near the stop codon or in the 3′ untranslated region. Here, it is reported that FIONA1 (FIO1), a human METTL16 ortholog, acts as a hitherto unknown m6A methyltransferase that determines m6A modifications at over 2000 Arabidopsis transcripts predominantly in the coding r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 46 publications
6
67
1
Order By: Relevance
“…In contrast, we identified significant depletion of U6 snRNA in the anti-m 6 A immunopurified RNA from fio1-1, fio1-3 and fio1-4 alleles (Figure 3B-C). These data are consistent with recent reports (Wang et al, 2022; Xu et al, 2022) indicating that Arabidopsis U6 snRNA is m 6 A-modified at the conserved position of the AC m6 A GA box and that this modification requires active FIO1.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast, we identified significant depletion of U6 snRNA in the anti-m 6 A immunopurified RNA from fio1-1, fio1-3 and fio1-4 alleles (Figure 3B-C). These data are consistent with recent reports (Wang et al, 2022; Xu et al, 2022) indicating that Arabidopsis U6 snRNA is m 6 A-modified at the conserved position of the AC m6 A GA box and that this modification requires active FIO1.…”
Section: Resultssupporting
confidence: 93%
“…This screen identified an early flowering mutant disrupting the gene encoding the Arabidopsis METTL16 orthologue, FIONA1 (FIO1) (Kim et al, 2008). We show that FIO1 is required for m 6 A modification of U6 snRNA, consistent with recent reports confirming this conserved function (Wang et al, 2022; Xu et al, 2022). We reveal the impact of FIO1 on MAF2 splicing and global patterns of gene expression.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…As for chromatin modifications, RNA methylation is deposited by ‘writers’ (RNA methyltransferases), removed by ‘erasers’ (RNA demethylases) and recognized by ‘readers’ (Liang et al ., 2020). Two m 6 A writers have been identified in plants, a methyltransferase complex composed of at least five proteins, namely mRNA ADENOSINE METHYLASE (MTA; ortholog of METTL3 in animals), METHYLTRANSFERASE B (MTB; ortholog of METTL14), FKBP12 INTERACTING PROTEIN 37 (FIP37; ortholog of WTAP), VIRILIZER (ortholog of WIRMA) and HAKAI (Yue et al ., 2019), that is responsible for the majority of mRNA methylation, and FIONA1 that deposits m 6 A at U6 snRNAs and at a subset of mRNAs (Sun et al ., 2022; Wang et al ., 2022; Xu et al ., 2022). Both writers have been associated with plant light signaling and light regulation of circadian clock entrainment (Kim et al ., 2008; Parker et al ., 2020; X. Wang et al ., 2021).…”
Section: Light‐driven Regulation Of the Epitranscriptomementioning
confidence: 99%
“…With regards to the second m 6 A writer, FIONA1, was first identified by a causative mutation in an Arabidopsis EMS genetic screen for early flowering (Kim et al ., 2008), but its molecular function as an RNA methyltransferase has emerged only recently (Sun et al ., 2022; Wang et al ., 2022; Xu et al ., 2022). In this seminal study, FIONA1 was reported to extend the period length of the expression of central oscillator genes including CIRCADIAN CLOCK ASSOCIATED 1 ( CCA1 ), LATE ELONGATED HYPOCOTYL ( LHY ) and TOC1 , and to increase mRNA levels of key flowering regulatory genes CONSTANS ( CO ) and FLOWERING LOCUS T ( FT ; Kim et al ., 2008).…”
Section: Light‐driven Regulation Of the Epitranscriptomementioning
confidence: 99%